Pelatihan Menulis Cerpen yang Berkearifan Lokal Pada Siswa SMAN 2 Prabumulih - Hayatun Nufus; Juaidah Agustina; Masnunah; Mardiana Sari; Ratu Wardarita; Sitti Rukiyah; Yenny Puspita (Jurnal Pengabdian Masyarakat Formosa, 2022)
Cerpen or short stories are literary works in the form of prose. Short stories are works of high level imagination. The formulation of the problem in this service is "How is the training to write short stories with local wisdom for students of SMAN 2 Prabumulih?" This activity is expected to benefit students, teachers, schools, and researchers. For students, this service is expected to foster enthusiasm and motivation for student learning, increase student interest in writing skills and develop students' ideas to think creatively in writing short stories with local wisdom. For teachers, it can add insight in learning to write, especially writing short stories. The methods used in this service are lectures, questions and answers, and the practice of making short stories with local wisdom. The results obtained in this community service are that students are interested in writing short stories. short story building elements.